2016
DOI: 10.1186/s12944-016-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipopoprotein antioxidant capacity, subpopulation distribution and paraoxonase-1 activity in patients with systemic lupus erythematosus

Abstract: BackgroundThe causes of increased cardiovascular risk in systemic lupus erythematosus (SLE) are not understood thoroughly, although presence of traditional cardiovascular risk factors and disease-specific agents were also proposed. In this study, we investigated the quantitative changes in the lipid profile, as well as qualitative characteristics of high-density lipoprotein (HDL) and markers of inflammation and disease activity in SLE patients.MethodsLipoprotein levels were determined in 51 SLE patients and 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 28 publications
1
46
0
5
Order By: Relevance
“…Chung et al reported that SLE patients have a lesser proportion of large HDL; however, the overall sizes of HDL were no different between SLE and healthy individuals . Other studies have also reported no significant differences in HDL size between SLE patients and healthy controls . Juárez‐Rojas et al reported that SLE patients tend to have lower proportions of HDL2b and higher proportions of HDL3b and HDL3c .…”
Section: Changes In Hdl Composition In Sle Patientsmentioning
confidence: 99%
“…Chung et al reported that SLE patients have a lesser proportion of large HDL; however, the overall sizes of HDL were no different between SLE and healthy individuals . Other studies have also reported no significant differences in HDL size between SLE patients and healthy controls . Juárez‐Rojas et al reported that SLE patients tend to have lower proportions of HDL2b and higher proportions of HDL3b and HDL3c .…”
Section: Changes In Hdl Composition In Sle Patientsmentioning
confidence: 99%
“…Recent clinical studies have investigated PON1 activity in systemic inflammatory diseases. A significant reduction in PON1 activity has been reported in patients with rheumatoid arthritis (RA) and patients with systemic lupus erythematosus (SLE) compared to healthy control subjects. In addition, decreasing PON1 activity has been found to be associated with increasing levels of SLE disease activity and end‐organ damage.…”
mentioning
confidence: 99%
“…Many studies have illustrated that anti oxidative capacity plays an important role in the severity of SLE (Gaál et al, 2016). In the current study, live P. chabaudi infection has resulted in a significant (P<0.05) increase in the level of total antioxidant capacity in the renal tissue of lupus mice in comparison to the control (Fig.4).…”
Section: Resultsmentioning
confidence: 99%